Work and precariousness in Brazilian museums: an introductory analysis (Cadernos de Sociomuseologia, 2016)
This study is an initial reflection on the situation of museologists workers in Brazil and is within the framework of the Labour Sociology. Use data from the survey conducted by the Brazilian Institute of Museums (IBRAM), Museums in Numbers, to view the status of museologists in museums institutions, locating such a situation a national and international economic scenario. Develop a brief foray into contemporary reflections on the world of work and its transformations, intending choose certain categories to characterize the museologists and understand them in the world of work. Will privilege studies of Brazilian sociologists Ricardo Antunes and Ruy Braga and English economist Guy Standing, because dealing with the issue of precarious work combining the references of Political Economy and Labour Sociology. Keywords: museologists, museums, precarization, precariat, work.